PENGARUH DIKLAT DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERASI (Sensus pada Pegawai Dinas Kesehatan Kabupaten Kaimana Provinsi Papua Barat) - Nema Woretma, Suprayitno & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2017)
District Health Office Kaimana, West Papua Province is an element of the conductof the District Government which is under and responsible to the Regent through theLocal Secretary constantly trying to improve employee performance, by carrying outtraining, increasing motivation and leadership. The purpose of research is to analyze thesignificance of the effect of training, motivation and leadership to employeeperformance. Analyzing the moderating effects of leadership on training and motivationinfluence on employee performance. This study uses census data types used arequantitative and qualitative data, the data source used primary data and secondary data.Population and sample in this study were all employees at the District Health OfficeKaimana, West Papua Province as many as 57 people, so it is a census study. Datacollection methods are used: questionnaires and documentation. Data analysistechnique used to test the validity, reliability test, classic assumption test and multiplelinear regression analysis, t-test, F, coefficient determination and test the absolutedifference. In conclusion, there was a significant effect of training on employeeperformance. There was a significant effect of motivation on employee performance.There was a significant influence on employee performance leadership. Leadership doesnot moderate training and motivation variables influence on employee performance.Keywords: training, motivation, leadership, employee performance.